KEANEKARAGAMAN DAN KEMERATAAN BURUNG PADA BERBAGAI TIPE HABITAT DI DESA ARTAIN KECAMATAN ARANIO KABUPATEN BANJAR KALIMANTAN SELATAN - Basuki Rahman; Abdi Fithria; Basir Achmad; Danang Biyatmoko (Lambung Mangkurat University-Indonesia, 2021)
Artain is a village located opposite the Riam Kanan reservoir in Aranio District, Banjar Regency, South Kalimantan Province. There are various types of habitat in the Village, from the edge of a reservoir to primary forest which is thought to be home to various birds species, which over time has the potential to degrade or change due to human activity which then reduces its quality and function as habitat for many birds species. It is necessary to research the diversity and evenness of birds in each habitat type in Artain, so that the existence of various bird species can be known. The research was conducted from May to June 2020, the method used in the study was the cruising circumference point, which is determining the observation point and its radius and then making observations by exploring the observation path continue. The results showed that there were 9 types of bird's habitat in Artain, they are Settlements, Periphery Reservoirs, Shrubs, Mixed Gardens, Rubber Gardens, Reeds, Fields, Secondary Forests, and Primary Forests. The lowest diversity value (H' = 1.25) was identified in field habitats and the highest (H' = 3.17) in scrub habitats, meaning that the level of diversity in all habitats was classified as moderate. The lowest evenness value in secondary forest habitats (E = 0.80) and the highest is mixed garden habitats and rubber gardens (E = 0.97), which means that evenness in each habitat is in the high category.